PENGARUH PENGETAHUAN KEWIRAUSAHAAN TERHADAP MINAT BERWIRAUSAHA MAHASISWA (STUDI KASUS: MAHASISWA PROGRAM STUDI MANAJEMEN FAKULTAS EKONOMI UNIVERSITAS KATOLIK SANTO THOMAS MEDAN) - Saragih, Nawary (Jurnal Manajemen dan Bisnis, 2020)
The purpose of this research is to know how big influence of entrepreneurial knowledge to entrepreneurship interests Student Program the Study of Faculty of Management of Saint Thomas Catholic University Medan. Research type used by descriptive and kuantitatif. Sampel research as much 96 Responder with the method of maximum sampling error intake from population conducted at random (random sampling). Data required to be collected through kuesioner by online. Method Analyse the data used is with the simple linear regression analysis. Result of research descriptively that entrepreneurial knowledge of Student Program the dominant Management Study agree equal to 51,04 % to entrepreneurial knowledge. While equal to 44,17 % that entrepreneurial knowledge can support the Student to hanker the entrepreneurship. Result of examination obtained: 1). Coefficient Determinasi ( R2) equal to its 0,230 meaning entrepreneurial knowledge able to explain the entrepreneurship interests of Student equal to 23,0 %, and 77,0 % is again influenced by other;dissimilar factor which is not explained this research (for example introductory sinergi entrepreneurial knowledge of Business, Makerting, e-commerce). 2). Equation of Regresi Y = 1.966+0,490+e. Where about mount the signifikan 0.000 < 0,05, by t-hitung equal to 5.306 > t-tabel equal to 1,65 hence Ho refused its meaning entrepreneurial knowledge own the influence which are positive and signifikan to entrepreneurship interests of Student. Suggested: 1). Because coefficient determinasi ( R2) still equal to its 0,230 meaning still lower the influence of entrepreneurial knowledge able to explain the entrepreneurship interests of Student, hence to support and also to grow the entrepreneurial knowledge of Student needed the make-up of items more aplikatif with the support sinergi from entrepreneurial knowledge other; dissimilar like Business. Marketing, e-commerce.2). Because reason appearance there still donot hanker and reason hanker the entrepreneurship from Student, hence to overcome it have righteously University of Roman of Santo Thomas Medan form the Unit of Student Co-Operation as training basin and or place learn the entrepreneurship for Student support they become the entrepreneurial to be getting out of unemployment later. 3). For the research of here in after better add the other; dissimilar variable outside this research which can explain the variable of dependen of entrepreneurship interests of Student like opportunity, personality, motivate the entrepreneurship, environmental of family after student become the collegiate and others